2014
DOI: 10.1186/1471-2466-14-69
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of pulmonary vascular reserve and right ventricular systolic reserve in pulmonary arterial hypertension

Abstract: BackgroundExercise capacity is impaired in pulmonary arterial hypertension (PAH). We hypothesized that cardiovascular reserve abnormalities would be associated with impaired hemodynamic response to pharmacological stress and worse outcome in PAH.MethodsEighteen PAH patients (p) group 1 NYHA class II/III and ten controls underwent simultaneous right cardiac catheterization and intravascular ultrasound at rest and during low dose-dobutamine (10 mcg/kg/min) with trendelenburg (DST). We estimated cardiac output (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
2
29
0
1
Order By: Relevance
“…RVWT is <5 mm in adults . Human and animal studies have shown that RVWT is a dynamic and varying parameter and is correlated with pulmonary arterial peak pressure, TAPSE, and some other echocardiographic parameters . The results of this study yielded a strong positive correlation between PAWT and RVWT (r = 0.893, P < 0.001).…”
Section: Discussionsupporting
confidence: 52%
“…RVWT is <5 mm in adults . Human and animal studies have shown that RVWT is a dynamic and varying parameter and is correlated with pulmonary arterial peak pressure, TAPSE, and some other echocardiographic parameters . The results of this study yielded a strong positive correlation between PAWT and RVWT (r = 0.893, P < 0.001).…”
Section: Discussionsupporting
confidence: 52%
“…Right ventricular failure can lead to liver function abnormalities, which increase the level of certain liver enzymes, such as transaminase and LDH, in the serum. Liver function is associated with the prognosis of patients with heart failure (10)(11)(12)(13). The aim of the present study was to determine whether S-LDH is a prognostic marker in patients with IPAH.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that only IVA and ΔIVA are significantly correlated to cardiac output (CO) and ΔCO. In contrast, S′ showed a moderate correlation and TAPSE did not correlate with CO [8]. Besides this, the lower values of TAPSE and S′ at rest in the PAH group compared with controls, as reported by SHARMA et al [1], illustrate the significant afterload dependence of TAPSE and S′, and hence, the inaccurate assessment of the contractile reserve.…”
Section: To the Editormentioning
confidence: 38%
“…LAU et al [10] showed that patients with PAH had an average dobutamine-induced mPAP-CO slope that was significantly higher than in healthy controls, with a markedly reduced distensibility coefficient α. Accordingly, we reported a significant increase of the elastic modulus (EM) of the pulmonary artery (PA) in PAH patients during pharmacological stress, with a negative change of EM in controls [8]. The positive correlation between ΔEM and ΔmPAP suggests that PA remodelling and buffering function impairment could be associated with the lower vascular reserve of PAH patients.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation